Clinical evaluation of affirm VPIII in the detection and identification of Trichomonas vaginalis, Gardnerella vaginalis, and Candida species in vaginitis/vaginosis. - Brown, Haywood L (2004)
OBJECTIVE: To compare the Affirm VPIII Microbial Identification Test for detection and identification of Candida species, Gardnerella vaginalis and Trichomonas vaginalis to clinical and microscopic criteria commonly used to diagnose vaginitis. METHODS: Women that were symptomatic for vaginitis/vaginosis and asymptomatic women being seen for routine obstetric or gynecological care were included in this study. Women treated with antibiotics or antifungals within one week or women who had douched within 24 hours were excluded. Two vaginal swab specimens were simultaneously obtained from each patient, one swab was placed in sterile physiological saline for immediate microscopic wet mount examination and KOH testing. The other swab was placed in the Affirm collection tube for Affirm VPIII testing based on previously demonstrated methods. RESULTS: The Affirm assay was significantly more likely to identify Gardnerella and Candida than wet mount. 190 (45%) were positive for Gardnerella by Affirm compared to 58 (14%) by wet mount; 45 (11%) were positive for Candida by Affirm compared to 31 (7%) by wet mount; and 30 (7%) were positive for Trichomonas by Affirm compared to 23 (5%) by wet mount. Symptomatic women were significantly more likely to be positive by Affirm only (23% vs. 10%), wet mount only (3% vs. 2%) or Affirm and wet mount (15% vs. 1%). Asymptomatic women were significantly more likely to be negative for Affirm and wet mount (43% vs. 5%). CONCLUSIONS: The Affirm VPIII test is a more sensitive diagnostic test for detection and identification of symptomatic vaginitis/vaginosis than conventional clinical examination and wet mount testing.